2015
DOI: 10.3174/ajnr.a4626
|View full text |Cite
|
Sign up to set email alerts
|

Different Functional and Microstructural Changes Depending on Duration of Mild Cognitive Impairment in Parkinson Disease

Abstract: BACKGROUND AND PURPOSE:The higher cortical burden of Lewy body and Alzheimer disease-type pathology has been reported to be associated with a faster onset of cognitive impairment of Parkinson disease. So far, there has been a few studies only about the changes of gray matter volume depending on duration of cognitive impairment in Parkinson disease. Therefore, our aim was to evaluate the different patterns of structural and functional changes in Parkinson disease with mild cognitive impairment according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Cortical thickness values may reflect several characteristics of intracortical morphology [41] and correlations between regions as demonstrated in our findings imply structural connectivity. However, these and similar data do not necessarily index physiological connectivity or activation patterns among networks in clinical populations [42]. Therefore, our results cannot be regarded as a definitive test of the importance of the central executive network in schizophrenia or in relation to cognitive impairment.…”
Section: Discussionmentioning
confidence: 83%
“…Cortical thickness values may reflect several characteristics of intracortical morphology [41] and correlations between regions as demonstrated in our findings imply structural connectivity. However, these and similar data do not necessarily index physiological connectivity or activation patterns among networks in clinical populations [42]. Therefore, our results cannot be regarded as a definitive test of the importance of the central executive network in schizophrenia or in relation to cognitive impairment.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, our colleagues recently reported a significant association between decreased fronto-striatal rsFC and a shorter duration of parkinsonism before MCI diagnosis in PD patients. The authors also found microstructural changes in the frontal white matter in PD-MCI patients with shorter disease duration, suggesting that the frontal area plays a pivotal role in deciding the rate of cognitive decline 27 . Our results also show an association between decreased rsFC in the frontal area and early cognitive decline in PD patients.…”
Section: Discussionmentioning
confidence: 89%
“…). Sensitivity analysis indicated to exclude 2 studies having a high risk of bias. After the exclusion of these primary studies the prevalence estimates remained stable (40%; n = 6813; 95% CI = 36–45; Q = 409.05, P < 0.0001; I 2 = 90.71%).…”
Section: Resultsmentioning
confidence: 99%
“…Sex. A total of 3 27,52,54 of 35 studies 4,5,11,12,14,15,[26][27][28][29][30][31][32][34][35][36][37][38][39][40][41][42][43][44][45][46][47][49][50][51][52][53][54]56,57 found an association between PD-MCI and male sex ( Supplementary Material 4). Our meta-analysis revealed a significant association between male sex and the occurrence of PD-MCI ( 4,10,12,14,33,38,39,[41][42][43]45,47,57 found an association between PD-MCI and a lower level of education ( Supplementary Material 4).…”
Section: Association With Demographic Characteristicsmentioning
confidence: 99%